Effect of benfotiamine on hepatic tissue levels of free calcium, copper, iron and zinc during CCl4-induced hepatotoxicity in rats - Aziz, Tavga Ahmed (Zanco Journal of Medical Sciences (ZJMS), 2011)
Background and Objectives: Toxic injury occurs in the liver more often than other organ, this can be attributed to the fact that virtually all ingested substances that are absorbed are first presented to the liver & that the liver is responsible for the metabolism and elimination of many substances. Carbon tetrachloride (CCl4) is very well known to cause hepatotoxicity that may be associated with impaired calcium and trace element homeostasis. This study was designed to evaluate the protective effect of benfotiamine against CCl4-induced disturbances in calcium, iron, copper and zinc homeostasis in liver tissue of rats. Methods: Liver tissue homogenate from normal controls, CCl4-treated and benfotiamine (70 mg/kg) pre-treated before induction of hepatic damage with CCl4 in rats were obtained, and processed for estimation of levels of free forms of calcium, iron, copper and zinc using atomic absorption spectrophotometry. Results: Analysis of data revealed significant elevation in calcium, iron and copper levels in hepatic tissue due to exposure to CCl4 compared to controls, while zinc levels not significantly affected. Pretreatment with benfotiamine results in significant decrease in calcium, iron and copper levels compared to non-treated group, while zinc levels found to be significantly elevated. Conclusions: Benfotiamine has a protective effect against CCl4-induced hepatic tissue damage which may be, in part, attributed to restoration of calcium and other trace elements homeostasis.